PENGELOLAAN RETRIBUSI PARKIR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH PADA DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA DI KABUPATEN NGAWI - Aris Tri Haryanto, Sumiati & (JI@P, 2017)
One levies selected by the District Government ngawi in tapping the financialresources of the area is through the withdrawal of parking fees at the edge ofthe public road, which is set in Ngawi District Regulation No. 3 of 2007 onBank Service Fees Parking Public Road. With the regulation of this area, isexpected to improve the effectiveness of regional revenue source in Ngawi.This research conducted in order to determine the management of parkingretribution in Ngawi conducted by the Department of Transportation,Communication, and Information Ngawi, as well as see the optimization of theparking fee collection. This type of research that be used is the descriptivetype that is a type of research that aims to outline systematic, factual andaccurate information on the existing data in the field of levies, focused on themanagement of existing parking charges in Ngawi. The data collection wasdone by interview and documentation study. Analysis of data using interactiveanalysis method according to Miles and Huberman. Based on the results ofresearch conducted, it can be seen that the process of managing parking feeswere managed by the Department of Transportation, Communication, andInformation Ngawi, from payments made by users of services to parkingattendants, payment of parking attendants to the concierge collector, receptionbendaraha then deposit on District government to be referred to as RegionalRevenue Ngawi sector, especially the parking levy.Keywords: Planning, Organizing, Implementation, Monitoring